Social Safety Nets in Fragile States : A Community-Based School Feeding Program in Togo - Andrews, Colin (World Bank, Washington, DC, 2017)
This paper reviews a small community-based school feeding program launched in Togo in response to the 2007/08 food price crisis. The discussion focuses on the operational and policy lessons emerging from the program, to better understand opportunities for scale up and sustainability in the future. A focus of the discussion is how to build safety nets in fragile states and in situations where there is weak and fragmented government capacity to deliver services to disadvantaged and vulnerable communities. In this context school feeding is explored as an entry point through the use of informal mechanisms based on the commitment of communities and civil society. The analysis is premised on quantitative and qualitative analysis carried out at program sites. The discussion identifies the operational challenges and opportunities in customizing school feeding within Togo with an emphasis on targeting, cost effectiveness, procurement and institutional aspects. Evidence on the economic and social benefits of the program is also presented, focusing on dietary impacts, as well as household and local community effects. The objective of the discussion is to share lessons learned from evaluation findings so that they can be useful for implementing similar programs in the future in Togo itself or in other countries. Findings from the analysis highlight the possibilities of implementing school feeding in a low capacity setting and the scope for using the program as a springboard towards a broader and more comprehensive social safety net.